Evaluation of Intermethod Reliability Between Online and In-Person Fitness Assessments Among Physically Inactive Adults - Pamela J. Wright; David Marshall; Kesheng Wang; Cynthia F. Corbett; Bhumi Patel (Journal of Nursing Measurement, 2026)
Background and Purpose: Online assessments are common. However, scarce research compares the accuracy of online assessments to in-person assessments. The purpose of this study was to evaluate the reliability of an online assessment versus an in-person fitness assessment. Methods: Participants ( N = 20) were recruited using flyers. They completed an online fitness assessment followed by an in-person fitness assessment 2–10 days later. Reliability was evaluated using intraclass correlation coefficients and Bland–Altman plots. Results: Participants were 30.8 (±20.2) years, mostly female (76.5%), and diverse in race/ethnicity with a body mass index of 23.4 kg/m 2 (±3.8). Statistically significant intraclass correlation coefficients were excellent for waist circumference (.93), hip circumference (.94), and push-up test (.94), and good for static squat test (.89) and curl-up test (.76). Conclusion: The online fitness assessment revealed high reliability when compared with an in-person fitness assessment.